2016
DOI: 10.4317/jced.52922
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in children with physical (Cerebral Palsy) and intellectual (Down Syndrome) disabilities: Systematic review I

Abstract: IntroductionTraditionally, patients with physical and/or intellectual disabilities presented greater oral pathology, owing to their condition and to other external factors. Improved social and health conditions make it necessary to update knowledge on their oral and dental health.Material and MethodsFor this purpose, a bibliographic review was done regarding the state of oral health of children with these two types of disability, in comparison with a control group. Some of the guidelines of the PRISMA statemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 9 publications
2
65
0
15
Order By: Relevance
“…This systematic review aimed to evaluate whether DS children/adolescents are more affected by malocclusion than non‐DS individuals. The literature has already recognized that the prevalence of periodontal outcomes among DS children/adolescents is higher than among individuals without DS . On the other hand, the prevalence of dental caries is lower among DS young individuals in comparison with non‐DS individuals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review aimed to evaluate whether DS children/adolescents are more affected by malocclusion than non‐DS individuals. The literature has already recognized that the prevalence of periodontal outcomes among DS children/adolescents is higher than among individuals without DS . On the other hand, the prevalence of dental caries is lower among DS young individuals in comparison with non‐DS individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Oral conditions, such as dental caries and periodontal disease among individuals with DS, have been largely discussed in the scientific literature by means of systematic reviews and meta‐analysis. No systematic attempt, however, has been carried out to summarize the evidence regarding the susceptibility to malocclusion among individuals with DS thus far .…”
Section: Introductionmentioning
confidence: 99%
“…The research done by Dieguez-Perez 10 showed that physically disabled children are prone to have poor oral hygiene which further leads to dental caries. Mentally disabled children have higher tendency to have gingival inflammation and deep gingival pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Mentally disabled children have higher tendency to have gingival inflammation and deep gingival pocket. 10 Mochizuki 11 research that was executed in year of 2007 suggested a routine plaque control for children with disability. Preventive and curative efforts are necessary regarding the fact that disabled children have higher level of poor oral hygiene than the normal children.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers play a vital role also in infants [12], children with disabilities [13,14], and elderly people [15,16]. Although nursing staffs are generally interested in improving the oral care of their caretakers, it has been recognized that their knowledge in this area is often inadequate.…”
Section: Introductionmentioning
confidence: 99%